Demokrasi dan Konstitualisme Hukum Islam di Indonesia - Kurniawan Kurniawan (Universitas Syiah Kuala, 2011)
ABSTRACT: Nowadays, Indonesia known as one of the huge democracy country in the world. The basic characteristic of democracy country is rule of law. Indonesia is a country that by law, put all the policies based on the source of all sources of law in Indonesia, namely the 1945 Constitution. Based on the law in idea, law in books and law in action can be concluded that based on the principle of religious divinity Almighty philosophical basis of the 1945 Constitution which concluded there is a strong recognition of the existence of the Islamic religion and Islamic law as a legal authority in Indonesia. Furthermore, in the perspective of the constitution there is a strong correlation between the state and Islam, including Islamic law that has become living law in the life of nation and state. The principles in the constitution to have any relevance to the principles that exist in Islamic law that stipulated in the Qur'an and Alhadits including the principles of justice, equality, and welfare. Therefore, Indonesia is set in a frame of Pancasila and 1945 Constitution can be viewed in the perspective of Islamic law as an effort to realize the law is set out in the Qur'an and Alhadits. Democracy and Constitutionalism of Islamic Law in Indonesia